New low speed airfoil families oriented towards horizontal-axis wind turbines applications - Abdelrahman, Mohammad; Hassanein, Atef (LAMBERT Academic Publishing, 2012)
The research discussed the effect of airfoil selection and its characteristic on wind turbine design and performance. It is found that the common aviation airfoil sections are not the proper choice for wind turbine rotors. So new airfoil families have been designed to meet the wind application requirements via a new code developed through the research work. The new airfoil families have been verified analytically on real rotors and the results have shown a promising increase in energy production up to 20%.